Economy and law of the constitutional design: the veil of disinterest - RENGIFO LOZANO, DIEGO (Universidad Santo Tomás, Bogotá-Colombia, 2016)
John Rawls, with ideas from political philosophy and the philosophy of law, and James Buchanan, withideas from economy, respectively have arrived to similar perspectives in terms of the construction of afair Constitutional order. By means of the well-known veils of ignorance and uncertainty, both Rawls andBuchanan may allow us to get round the apparently unavoidable feature in the individual behaviour: the“personal interest”, which seems to be the fundamental issue in regard to the collective character of thejustice concept.